A comparison of the production of antimicrobial peptides and proteins by Galleria mellonella larvae in response to infection with two Pseudomonas aeruginosa strains differing in the profile of secreted proteases. (May 2021) - Andrejko, Mariola; Mak, Paweł; Siemińska-Kuczer, Anna; Iwański, Bartłomiej; Wojda, Iwona; Suder, Piotr; Kuleta, Paula; Regucka, Karolina; Cytryńska, Małgorzata
Graphical abstract: Highlights: A broad set of antimicrobial peptides was detected in Pseudomonas -infected larvae. In the insect hemolymph 13 antimicrobial peptides and proteins were identified. The level of 6 AMPs depended on the strain and medium used for bacterial growth. Bacterial proteases secreted during infection influenced AMPs level in hemolymph. Abstract: The work presents identification of antimicrobial peptides and proteins (AMPs) in the hemolymph of Galleria mellonella larvae infected with two Pseudomonas aeruginosa strains (ATCC 27, 853 and PA18), differing in the profile of secreted proteases. The insects were immunized with bacteria cultivated in rich (LB) and minimal (M9) media, which resulted in appearance of a similar broad set of AMPs in the hemolymph. Among them, 13 peptides and proteins were identified, i.e. proline-rich peptides 1 and 2, lebocin-like anionic peptide 1 and anionic peptide 2, defensin/galiomicin, cecropin, cecropin D-like peptide, apolipophoricin, gallerimycin, moricin-like peptide B, lysozyme, apolipophorin III, and superoxide dismutase. Bacterial strain- and/or medium-dependent changes in the level of proline-rich peptide 1, anionic peptide 1 and 2, moricin-like peptide B, cecropin D-like and gallerimycin were observed. The analysis of the expression of genes encoding cecropin, gallerimycin, and galiomicin indicated that they were differently affected by the bacterial strain but mainly by the medium used for bacterial culture. The highest expression was found for the LB medium. In addition to the antibacterial and antifungal activity, proteolytic activity was detected in the hemolymph of the P. aeruginosa -infected insects. Based on these results and those presented in our previous reports, it can be postulated that the appearance of AMPs in G. mellonella hemolymph can be triggered not only by P. aeruginosa pathogen associated molecular patterns (PAMPs) but also by bacterial extracellular proteases secreted during infection. However, although there were no qualitative differences in the set of AMPs depending on the P. aeruginosa strain and medium, differences in the level of particular AMPs synthesized in response to the bacteria used were observed.